Optimization analysis of NURBS curved variable stiffness laminates with a hole. (June 2022) - Cao, Zhongliang; Lin, Guojun; Shi, Qinghe; Cao, Qinglin
Abstract: Based on cubic NURBS curve, the optimization design of the variable stiffness laminates with a hole are carried out. Firstly, the reference trajectory of the fiber prepared by variable angle placement is defined by cubic NURBS curve, and the parameterized expression of variable-angle fiber placement is derived. Secondly, the linear buckling analyses of all constant stiffness laminates with a hole are carried out to obtain the constant stiffness laminates with the maximum first-order buckling load, the ± 45° placement of the constant stiffness laminates with a hole is replaced by the variable-angle fiber placements. The linear buckling analysis of the variable stiffness laminates with a hole is carried out. Then, the radial basis function is used to build an optimization model to optimize the variable stiffness laminates with a hole. Finally, under the constraints of curvature radius, MATLAB is used to conduct the optimization of variable stiffness laminates with a hole, and the optimal results under different curvature constraints are obtained. The results show that the buckling load coefficient of [±<10(0.1)(0.6)(0.6)53 > ]2sH laminates is 32.93% higher than that of [45/−45]2sH laminates. Using cubic NURBS curve to design laminates with a hole can avoid stress concentration and improve the buckling property of laminates with a hole. Graphical Abstract: ga1 Highlights: Based on cubic NURBS curve, the optimization design of the variable stiffness laminates with a hole are carried out. ABAQUS is used to model the variable stiffness laminates with a hole. The radial basis function is used to construct the optimization model, and the optimal results under different curvature radius constraints are obtained through optimization. The buckling property of constant stiffness laminates with a hole, constant stiffness laminates and variable stiffness laminates with a hole are analyzed and compared.